Major histocompatibility complex class II polymorphic variants are associated with asthma predisposition in the Punjabi population of Lahore, Pakistan - Aslam, Raheela; Shahid, Mariam; Bano, Iqbal; Ayoub, Muhammad; Sabar, Muhammad Farooq; Altaf, Saba; Kousar, Samra; Ghani, Muhammad Usman; Husnain, Tayyab; Shahid, Ahmad Ali (The clinical respiratory journal, 2021)
Introduction Various genome wide association studies have manifested that Major Histocompatibility Complex (MHC) region on chromosome 6p21 houses many potential candidate genes for asthma. Objective This Case‐Control association study was planned to determine the association of 10 Single Nucleotide Polymorphisms (SNPs), residing within and around MHC genes’ region on chromosome 6p21, with Asthma in Punjabi population of Lahore, Pakistan. Methods A total of 161 subjects, 61 physician‐diagnosed asthma patients and 100 age‐matched healthy controls, were recruited from Lahore, a city in Punjab. Ten single nucleotide polymorphisms (SNPs) (rs9378249, rs2070600, rs404860, rs6689, rs1049124, rs1063355, rs1049225, rs1049219, rs7773955 and rs928976) located within or near AGER, NOTCH and HLA genes in MHC region, were genotyped in both patients and controls using single base extension reaction and capillary electrophoresis‐based genetic analyser. Statistical models were applied using SHEsis Plus. Results were adjusted for various cofactors (age, gender and environment) and by applying multiple corrections. Haplotype and linkage disequilibrium analyses were performed on Haploview software v4.1. Results Three of the studied SNPs rs1049124, rs1049219 and rs7773955 show independent significant association with asthma under allelic and genotypic models. Two of the haplotypes, H7 and H13, “CTAATTT” and “CCACTAT”, respectively, for rs2070600, rs404860, rs6689, rs1049124, rs1063355, rs1049219 and rs7773955, are found to be significantly associated with the disease. Conclusion This study reports association of SNP variants residing on HLA‐DQB1 and HLA‐DQA2 genes and haplotypes H7 and H13 on genomic region 6p21 with Asthma in the Punjabi population of Lahore, Pakistan.